Karakterisasi Uwi-Uwian (Dioscorea spp) Dari Banjarnegara Berdasarkan Penanda Morfologi - Pertiwa, Susy Ika; Jumari, J; Wiryani, Erry (Bioma : Berkala Ilmiah Biologi, 2018)
The diversity of Dioscorea spp. both inter-species and intra-species are spreaded in several areas in Central Java, including Banjarnegara.  Dioscorea is a  plant that has the potentials to be developed and cultivated. The purposes of this reasearch are to identify the species, characterize the morphological characters (stem, leaf, and tuber) of eight varians Dioscorea spp from Banjarnegara. The sample used in this reasearch are the eight varians of Dioscorea spp from Banjarnegara.  The Identification was done by using a identification keys. Characterization of morphological characters was done by using the guidebook of Descriptor for Yam. The results showed that eight cultivars of Dioscorea spp are grouped into two types: Dioscorea alata and Dioscorea esculenta. Dioscorea alata has a stem which rotate the to the right, rectangular shaped of stem, it’s has wing and doesn’t have a spin, elongated heart-shaped leaves, oval-oblong and round shaped tuber. Dioscorea esculenta has a stem which rotate to the left, rounded shaped of stem, it has not wing but spiked, dilated heart-shaped leaf, and oval shape tuber.  Keywords: Dioscorea spp, identifikasi, characteristic, morphology,